Acetylcholine receptor γ-subunits mRNA isoforms expressed in denervated rat muscle - Amanda M. Li (2018)
The fetal acetylcholine (ACh) receptor, composed of the αβγδ subunits, is expressed in fetal, neonatal, and denervated muscle. Single-channel recording has revealed three kinetically distinct classes in neonatal and denervated muscle, suggesting that at least three forms of the γ-subunit are required. To account for the kinetic classes observed, we compared the messenger ribonucleic acid (mRNA) forms expressed in neonatal and denervated muscle using reverse transcriptase polymerase chain reaction, cloning, and RNAse protection assays. We found five novel forms arising from alternative splicing, which we named γ5-γ9. The forms γ5, γ6, and γ7 lack exon 4 and 63-, 89-, and 136 bp of exon 5, respectively. A γ8 form lacks exons 3 and 4 and 19 bp of exon 5. The last, γ9, lacks exons 3, 4, and 5. Results indicate that γ4 predominates in fetal muscle and γ7 in denervated adult muscle. Some of the γ-subunit mRNAs found may generate the receptors observed in muscle. © 2008 Humana Press Inc.